SIKAP MASYARAKAT SUKU AKIT TERHADAP PENDIDIKAN DESA JANGKANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Ropik, Ahmad; Umari, Tri; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to find out of society attitude suku akit toward of his education and to find out the problem of the children in education. The population sampel of this research estimate 30 of head family and from the total of society attitude suku akit estimate 133 of head family. The result of this research show that the component of cognitif, afektif and konatif of society attitude of suku akit toward education in jangkang village, kecamatan bantan, kabupaten bengkalis, is classified good categories is 66,86%, 75.33% and 66.86%. in the other hand, the problem that caused of children suku akit in education clasified high estimate 76.93%. so the problem that faced is economic problem, parent attentions and children interested to school by theirself.Keyword: attitude, suku akit, education.